(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The aim of this work is to research the performance of nano TiO_2 photocatalyst on physical & chemical properties of cotton fiber. Different concentration of photocatalyst was finished on the cotton fabric by finishing process. The UV light and the natural light were used as the light source to irradiate the fabric. By determining the fiber's polymerization degree, crystallinity, as well as the fabric's breaking strength, tear strength and K/S value, the influence of the nano TiO_2 photocatalyst on the physical & chemical properties and the colour of the cotton fiber were measured.